Investigation of Air Inflow Distribution Nature in Boiler Gas Flue - V. I. Nazarov; A. A. Khadorik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The paper presents results of mathematical investigations on distribution of air inflows in the ТП-87 boiler gas flue. Experiments have been executed on the basis of programming «Flow Vision» complex.